Seafood Discards: A Potent Source of Enzymes and Biomacromolecules With Nutritional and Nutraceutical Significance - Nag, Moupriya; Lahiri, Dibyajit; Dey, Ankita; Sarkar, Tanmay; Pati, Siddhartha; Joshi, Sanket; Bunawan, Hamidun; Mohammed, Arifullah; Edinur, Hisham Atan; Ghosh, Sreejita; Ray, Rina Rani (Frontiers in Nutrition, 2022)
In recent times, the seafood industry is found to produce large volumes of waste products comprising shrimp shells, fish bones, fins, skins, intestines, and carcasses, along with the voluminous quantity of wastewater effluents. These seafood industry effluents contain large quantities of lipids, amino acids, proteins, polyunsaturated fatty acids, minerals, and carotenoids mixed with the garbage. This debris not only causes a huge wastage of various nutrients but also roots in severe environmental contamination. Hence, the problem of such seafood industry run-offs needs to be immediately managed with a commercial outlook. Microbiological treatment may lead to the valorization of seafood wastes, the trove of several useful compounds into value-added materials like enzymes, such as lipase, protease, chitinase, hyaluronidase, phosphatase, etc., and organic compounds like bioactive peptides, collagen, gelatin, chitosan, and mineral-based nutraceuticals. Such bioconversion in combination with a bio-refinery strategy possesses the potential for environment-friendly and inexpensive management of discards generated from seafood, which can sustainably maintain the production of seafood. The compounds that are being produced may act as nutritional sources or as nutraceuticals, foods with medicinal value. Determining utilization of seafood discard not only reduces the obnoxious deposition of waste but adds economy in the production of food with nutritional and medicinal importance, and, thereby meets up the long-lasting global demand of making nutrients and nutraceuticals available at a nominal cost.